Bilateral Renal Colic as an Initial Presentation of Erdheim-Chester Disease - Julien Sarkis; Fady Haddad; Sarah Nasr; Elie Hanna; Ahmad Mroueh; Elie Nemr (Case Reports in Urology)
Erdheim-Chester disease (ECD) is a rare non-Langerhans cells histiocytosis characterized by multiorgan involvement, with renal-ECD documented in over one-third of patients. Renal disease is generally asymptomatic, rarely causing hydronephrosis and kidney impairment. In addition, the diverse clinical picture of Erdheim-Chester disease arises slowly with sequential manifestations. We present a rare case of a 75-year-old woman on long-term treatment for panhypopituitarism and steroid therapy for vasculitis, presenting to the emergency department with bilateral renal colic and acute kidney injury. Abdominopelvic CT scan revealed renal infiltration with signs of retroperitoneal fibrosis and hydronephrosis. Kidney CT-guided biopsy and 18-fluorodeoxyglucose (FDG) positron emission tomography whole body scan as well as the history of hypopituitarism and vasculitis confirmed the diagnosis of Erdheim-Chester disease. Proper therapy with interferon-α was started. This case describes the multifaced manifestation of this disease and the difficulty to establish the diagnosis, as well as the pivotal role that a urologist can play in its management.